Searching for a distant God: the legacy of Maimonides - Seeskin, Kenneth (Oxford University Press, 2000)
Monotheism is usually considered Judaism's greatest contribution to world culture, but it is far from clear what monotheism is. This work examines the notion that monotheism is not so much a claim about the number of God as a claim about the nature of God. Seeskin argues that the idea of a God who is separate from his creation and unique is not just an abstraction but a suitable basis for worship. He examines this conclusion in the contexts of prayer, creation, sabbath observance, repentance, religious freedom and love of God. Maimonides plays a central role in the argument both because of his importance to Jewish self-understanding and because he deals with the question of how philosophic ideas are embodied in religious ritual